Peran Guru Dan Orang Tua Di SD Dalam Pembelajaran IPS Dimasa Pandemi Covid-19 - Komang Surya Adnyana; Gusti Ngurah Arya Yudaparmita (STAHN Mpu Kuturan Singaraja, 2021)
Social studies learning is learning related to social relationships. Social studies learning is also related to human and community interactions at school and outside of school. Meanwhile, distance learning greatly limits social activities due to health protocols, so this certainly has an impact on the learning process, including social studies learning in elementary schools. Moreover, social studies learning which teaches students related social and citizenship issues, of course, is quite difficult to teach through distance learning and in conditions of limiting social activities. Some of the obstacles experienced by students are the limited time in the online learning process, the difficulty of students in understanding the learning material delivered by the teacher, network constraints which are sometimes less stable and the home atmosphere which is sometimes less conducive to learning. In addition, students feel very bored in the social studies learning carried out by the teacher. Keywords: The Role of Teachers, Parents, Social Studies Learning